2019
DOI: 10.22377/ajp.v13i02.3111
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background: Olive leaf, a versatile plant obtained from Olea europaea which was enriched with various secondary metabolites likes polyphenols, secoirodiods eg. Oleuropein, Hydroxytyrosol etc. Current treatment modalities for meningitis were ended up with MDR. Hence, a new strategy is mandate to alleviate bacterial meningitis. Objective: Current research structured to identify the potential of Oleuropein loaded NLC in the inhibition of Bacterial Meningitis. Glycerol is used as bio-solvent in hot blanching assis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In light of the characterization results, NLC-OLE50 seemed to be a promising carrier for OLE with enhanced antioxidant activity and thus we continued to study its efficacy in lung epithelial cell models. Several authors have reported micro-and nanoencapsulation methods for olive leaf extracts but to the best of our knowledge, there is a lack of studies regarding the impact that the formulation process could have on the bioactivity of this polyphenol in a biological system [22,23,52].…”
Section: Cell Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of the characterization results, NLC-OLE50 seemed to be a promising carrier for OLE with enhanced antioxidant activity and thus we continued to study its efficacy in lung epithelial cell models. Several authors have reported micro-and nanoencapsulation methods for olive leaf extracts but to the best of our knowledge, there is a lack of studies regarding the impact that the formulation process could have on the bioactivity of this polyphenol in a biological system [22,23,52].…”
Section: Cell Experimentsmentioning
confidence: 99%
“…In this context, micro and nanoencapsulation technologies have been proposed as promising strategies [20]. Currently, some encapsulation methods for Olea europaea leaf extracts have been described such as W/O nanoemulsions and W/O/W double emulsions [21][22][23], spray-drying [24,25], formation of inclusion complexes with cyclodextrin [26], electrostatic extrusion [27], biopolymer complexes/double emulsions [21], and liposomes [28]. However, they have some limitations such as the use of organic solvents, tedious and time consuming manufacturing processes, high particle sizes, and low yield (for spray drying).…”
Section: Introductionmentioning
confidence: 99%
“…All measurements were made in triplicate at 25 °C. The zeta potential was then directly determined from the equation by using the Smolochowski equation as follows [ 80 , 81 ]. ζ = εµ/η where ζ is the zeta potential, µ is the electrophoretic mobility, ε is the electric permittivity of the liquid, and η is the viscosity of the liquid.…”
Section: Methodsmentioning
confidence: 99%